2001
DOI: 10.1029/2000jc000461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent entrainment of air bubbles by breaking wind waves on ocean reflectance and underwater light field

Abstract: Abstract. Light-scattering properties of air bubbles suspended in water and observational evidence of bubble entrainment by breaking wind waves indicate that bubble clouds may influence ocean reflectance and in-water light field characteristics within the surface layer. We estimate potential changes in remote sensing reflectance and in-water light field associated with a bubble entrainment event observed at a wind speed of 10 rn s -•. Our approach combines acoustic measurements of bubble concentration as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…In this case it has to be assumed that in reality the lensing efficiency is considerably reduced because of nonlinear hydrodynamic interactions at the surface and air bubbles that are induced by breaking waves (e.g. Stramski and Tegowski, 2001). Thus, it has to be assumed that at high wind speed our model overestimates the strength of irradiance variability down the water column.…”
Section: Discussion Of the Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case it has to be assumed that in reality the lensing efficiency is considerably reduced because of nonlinear hydrodynamic interactions at the surface and air bubbles that are induced by breaking waves (e.g. Stramski and Tegowski, 2001). Thus, it has to be assumed that at high wind speed our model overestimates the strength of irradiance variability down the water column.…”
Section: Discussion Of the Simulation Resultsmentioning
confidence: 99%
“…More relevant are air bubbles in the upper water layer as they cause enhanced reflectance (in clear water the reflectance has a strong dependence on the light spectrum). But in contrast to the upwelling light, bubbles induce only very small enhancement in downwelling irradiance within the top several tens of centimetres just beneath the surface and below that layer, E d is reduced compared to bubble-free water (Stramski and Tegowski, 2001). For this reason we must consider that air bubbles in water impair the effectiveness of wave lensing, and thus damp the intensity of the described fluctuations, in particular at increasing wind speed.…”
Section: Direct Influence Of Local Wind Conditionsmentioning
confidence: 99%
“…Strong typhoon winds may induce massive entrainment of air bubbles into the water column through the wave breaking; these bubbles have a spectral effect on ocean reflectance, and therefore, the bubble entrainment may affect the estimation accuracy of surface Chl-a concentration from remote sensing observations [40]. In situ measurements from a Bio-Argo float with fluorescence method to detect the Chl-a concentration located at the central Bay of Bengal indicate that there was substantial Chl-a increase (to as high as 4.5 mg·m −3 ) induced by a tropical cyclone, Hudhud, and the Bio-Argo observations on the Chl-a profiles suggest that the nutrient inject is a major reason for the Chl-a increase under the storm condition, leading to the chlorophyll bloom [41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al (1998) found that organic coatings on bubbles will significantly enhance the backscattering and proposed that bubbles could be the strongest contributor to the light coming out of ocean. Stramski and Tegowski (2001) illustrated the temporal variation of the light field caused by bubble injection under a wave breaking event (wind speed = 10 m s −1 ) recorded by an acoustic backscatter in coastal waters and found a > 2-fold increase in reflectance (400-700 nm) over time periods on the order of several minutes or less. Clearly, ocean surface reflectance patterns can be altered by immersed bubbles under windy conditions, which may further affect satellite aerosol retrievals from passive sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Within a pixel of satellite observation, whitecaps are sporadic and scattered whereas bubbles in water form a more or less uniform layer that could exist over regions that are free from whitecap contamination (e.g., Monahan and Lu, 1990). While whitecaps serve as a diffuse reflector, reflecting solar radiation directly at the surface (Frouin et al, 1996;Whitlock et al, 1982), bubbles interact with light below the surface, enhancing water-leaving radiance (Stramski and Tegowski, 2001;Terrill et al, 2001;Zhang et al, 1998). Studies have shown that the contributions of bubbles to water-leaving radiance are rather significant.…”
Section: Introductionmentioning
confidence: 99%